Fault-tolerant routing through the 'Umbrella' protocol. (10th December 2007) - Sotiriou, Athanasios-Dimitrios; Kalliaras, Panagiotis; Mitrou, Nikolas
Routing protocols have always been the backbone of modern networks. The introduction, however, of new topologies, such as Peer-to-Peer (P2P) and ad-hoc networks, have increased demands for efficient algorithms that can provide fault-tolerant operation under highly-distributed environments. In this paper, we provide proof for a novel routing protocol, the 'Umbrella' protocol, which can operate efficiently under constantly changing environments. The novelty of our scheme is based on a fixed-sized Distributed Hash Table (DHT), which allows for increased scalability. We mainly focus on content distribution and provide algorithms and a number of extensions for successful publishing and retrieval of keywords on top of an overlay network.